Online Children’s Book to Encourage Extensive Reading in English Teaching in The Islamic Family Law Program Study of IAI Tasikmalaya - Fajri, Laili Rahmatul (Manajerial | Journal Manajemen pendidikan islam, 2022)
The use of online children’s book to encourage students in extensive reading is one of creative strategies since it can improve students’ interests in reading. As English books that are difficult to find, many books are unaffordable for many people, and they also lack variety in terms of English levels and genre, online children’s book that is provided in story weaver platform can help students to get a wide variety of reading materials. Therefore, this paper explores the author’s experience in implementing online children’s book to encourage extensive reading in English Teaching during one semester in the Islamic Family Law Program Study and analyzing the students’ perception of the use of online children’s book in extensive reading practice. The participants are students of the second semester who take English 2 course. In this research, qualitative is used as a research method. The result showed that the students have positive attitudes towards online children’s book when they have to read extensively.